Unformatted text preview: f ( x ) = 2 + 3 x . Find the derivative f p ( x ) by following the steps below. (a) f ( x + h ) = (b) Find and simplify. f ( x + h )f ( x ) = (c) Using (b), ±nd and simplify. f ( x + h )f ( x ) h = (d) lim h → f ( x + h )f ( x ) h = (e) What is f p (3)?...
View
Full
Document
This note was uploaded on 08/16/2011 for the course MATH 131 taught by Professor Siebert during the Spring '08 term at Ohio State.
 Spring '08
 SIEBERT
 Math, Limits

Click to edit the document details